ANALISIS KUALITAS PELAYANAN ROOM ATTENDANT DI ROCKY PLAZA HOTEL PADANG - Fitry, Herma; Chair, Ira Meirina; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this research is to determine the quality of room attendantservice at Rocky Plaza Hotel in terms of 5 indicators of service quality, namely:reliability, responsiveness, assurance, empathy and tangibles . The method whichwas used in this research was descriptive quantitative. The population of thisstudy was guests staying at the Rocky Plaza Hotel Padang, with an averagenumber of guests as many as 5001 people. Sampling technique in this research ispurposive sampling counted 98 guests. The data were collected through aquestionnaire using likert scale which validity and reliability have been tested.The result of the research demonstrates that overall service quality at Hotel RockyPlaza Padang was classified as a good category with the visitor percentageof 54%.While for each indicator are: 1) tangibles as much as 54% of respondents statedgood, 2) empathy as much as 59% respondent stated enough, 3) reliability 48% ofrespondents stated enough, 4) Responsiveness as many as 49% of respondentsstated enough, 5) assurance as much as 50% of respondents stated good.